PENGARUH EXPERIENCE MARKETING, KEPERCAYAAN KONSUMEN, DAN KEMUDAHAN PENGGUNAAN TERHADAP MINAT BELI ULANG DI MARKETPLACE SHOPEE - Sari, Lusia Luwanda; Panjaitan, Fery; Novika (Jurnal Progresif Manajemen Bisnis, 2023)
The results showed that Experience Marketing had a significant positive effect on Repurchase Intention, Consumer Trust had a significant positive effect on Repurchase Intention, and Ease of Use had no significant positive effect on Repurchase Interest in the Shopee Marketplace. T-test and F-test are shown here with R2 : The Experience Marketing variable (X1) based on the results of a comparison where tcount is 5.166 > ttable 0.2769 and a significant value is 0.001 <0.1, it is concluded that the Experience Marketing variable has a positive effect on Repurchase Interest in the Shopee Marketplace. The Consumer Trust Variable (X2) based on the results of a comparison where tcount 4.464 > ttable 0.2769 and a significant value of 0.001 <0.1, it is concluded that the Trust variable has a positive influence on Repurchase Interest in the Shopee Marketplace. The Ease of Use variable (X3) based on the results of a comparison where tcount is 0.062 < ttable 0.2769 and a significant value is 0.950 < 0.1, it is concluded that the Ease of Use variable does not have a positive effect on Repurchase Interest in the Shopee Marketplace. The F test is compared to Fcount > Ftable with a significance of 0.001 < 0.1, so it is concluded that the independent variables have a simultaneous influence on the dependent variable on Repurchase Interest in the Shopee Marketplace. This coefficient is used to see how much the independent variable is used and can explain the dependent variable.